2012
DOI: 10.1007/s00068-012-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of amputation injuries in the Austrian helicopter emergency medical service: a retrospective, nationwide cohort study

Abstract: In the HEMS, amputation injuries are infrequent and mostly not life-threatening. However, HEMS crews need to maintain their focus on providing sufficient and fast primary care while facilitating rapid transport to a specialized hospital. The knowledge of the epidemiological characteristics of amputation injuries encountered in the HEMS gained in this study may be useful for educational and operational purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
5
1
5
Order By: Relevance
“…Frank et al 3 described amputations in 1 finger in 16 cases, comparable to the 13 cases of thumb amputation without involvement of the other fingers found in the present series. Selig et al 5 described reimplantation in 28% of amputation cases, a value well below the 65.7% found in the cases in the present study corresponding to 23 patients. The only mention of macroreimplants is made by Frank et al, 2 who described one case at the level of the hand, similar to our findings (one hand macroreimplant and two at the level of the wrist).…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Frank et al 3 described amputations in 1 finger in 16 cases, comparable to the 13 cases of thumb amputation without involvement of the other fingers found in the present series. Selig et al 5 described reimplantation in 28% of amputation cases, a value well below the 65.7% found in the cases in the present study corresponding to 23 patients. The only mention of macroreimplants is made by Frank et al, 2 who described one case at the level of the hand, similar to our findings (one hand macroreimplant and two at the level of the wrist).…”
Section: Discussioncontrasting
confidence: 69%
“…Circular saw injuries occur predominantly in males, possibly due to the association with woodwork activities, which are typically performed by men. Frank et al 2 3 described a sample of 114 patients, with only 8 females, while Selig et al 5 reported a male predominance with a ratio of 7:1, and Sabongi et al 6 reported a sample composed of 98.1% of male patients. Fikry et al 1 and Hassine et al 4 reported an exclusively male sample, similar to that observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor: Amputation injuries are rarely seen in helicopter emergency medical services missions, and complete amputations even less so. 1 Although it has been reported that the most frequently injured part of the lower limb for skiers is the knee, no case of amputation has yet been reported among 13,381 lower extremity skiing injuries. 2 We recently had to face a dramatic avalanche accident resulting in complete traumatic leg amputation, which is the first case that we are aware of described to date.…”
Section: Avalanche Accident Resulting In Leg Amputationmentioning
confidence: 99%